Treatment of Decubitus Ulcer - Ohhira, Osamu; Aoki, Satoru; Hashimoto, Yuichi; Takeshita, Noritaka (Orthopedics & Traumatology, 1988)
Local flap, muscle flap and musculocutaneous flap are mainly used in the surgical management of decubitus ulcer, though there are many surgical procedures. We have treated eleven cases of the decubitus ulcer with these flaps and satisfactory results were obtained in the shortterm follow-up study.